The main tendencies of discourse representation of immigrant workers in Malaysia: a critical discourse analysis in The Star and Malaysiakini online news portals - Mohd Sobri Paridaluddin, Noorfarida Filzah; Md Zamin, Ainul Azmin (IIUM Press, 2023)
Being one of the most industrialised nations in Southeast Asia, Malaysia has been receiving many immigrant workers from neighbouringcountries to provide labor for the economic expansion. The government was heavily criticised following its announcement on the intake of 1.5 million Bangladeshi workers into the country. The local media have profoundly reported on the issues of immigrant workers in Malaysia. This study focuses on the main tendencies of discourse representation of immigrant workers in Malaysia, specifically in The Star and Malaysiakini online news portals. A total of 20 news articles, 10 from each news portal concerning the issues of migrant workers from year 2016 to early 2017 are analysed according to Fairclough’s (1995) Discourse Representation in Media Discourse framework. Each phrase undergoes five level parameter analysis to investigate the language and the strategies employed. This research is to identify the main tendenciesof discourse representation of immigrant workers in Malaysia in The Star Online and Malaysiakini. As a whole, both online news portals maintained the ideational meaning of the primary discourse in their news reports